Czy są nam potrzebni „marni” poeci? - Czajkowska, Agnieszka (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The paper contains reflections on the historical circumstances of the evaluation of artistic work, which guarantee immortality to one author, and condemn others to oblivion. The author takes into account the popularity of poetry which is not of the highest quality, and which is present in mass culture. Poems by less known, mediocre poets appear as lyrics of national or religious songs . Examples of the 19th and 20th century literature have been provided, including works of Michał Bałucki, Jan Czeczot, Maria Konopnicka, Franciszek Karpiński, Teofil Lenartowicz, Władysław Syrokomla, Stefan Witwicki and others. The study emphasizes the unconsciousness of readers and users as to the authorship, circumstances of the creation, as well as the original purpose of the texts that are read and sung to this day. As a result of the analysis, it turns out that popular culture can store valuable content and is an important reservoir of national culture.
Do We Need Weak Poets?
Keywords: poet; popularity; value of literature; mass culture; song; poeta; popularność; wartość literatury; masowość; piosenka